Magnetic properties of multiwall nanotubes - Glenis, S.; V. Likodimos; Guskos, N.; Lin, C.L. (Journal of Magnetism and Magnetic Materials, 2004)
The diamagnetic susceptibility of multiwall carbon nanotubes is studied as function of magnetic field and temperature. Both the low-field and the low-temperature susceptibility reveal a definite paramagnetic upturn in qualitative agreement with the Aharonov-Bohm effect. Analysis of the high-field magnetic susceptibility in terms of the orbital diamagnetism of quasi-two-dimensional graphite implies hole-doping and supports further the intrinsically divergent paramagnetic contribution of small metallic nanotubes. © 2003 Elsevier B.V. All rights reserved.